2018
DOI: 10.3390/geosciences8030091
|View full text |Cite
|
Sign up to set email alerts
|

Seabed Morphology and Sedimentary Regimes defining Fishing Grounds along the Eastern Brazilian Shelf

Abstract: Shelf morphology and sedimentary regimes are influenced by processes operating at different temporal and spatial scales and are important records of sea level changes and sediment supply and/or carbonate production. The northern continental shelf of Espírito Santo (Brazil) contains evidence of different sedimentary regimes that distribute diverse and complex marine habitats. Herein, seabed morphology, acoustic images of the seafloor (side scan sonar and sub-bottom profiler), and sediment samples were used to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 39 publications
2
14
0
1
Order By: Relevance
“…Dias (2000) reported that the maerl and Lithothamnium alga banks are better developed in the 8 to 60m depth interval, where the algae take better advantage of light intensity and penetration, providing the ideal conditions for their development. The records and distribution of maerl and Lithothamnium coralline algae in the study site corroborate the findings of Dias (2000) and other studies (Albino, 1999;Bourguinon et al, 2018) in this area. The maerl and Lithothamnium banks associated with fragments of rhodoliths and biolitoclastic sediments occur from 40 to 60 m deep in the submerged channels of the Costa das Algas EPA, forming the Bioclastic sand (Bs) sedimentary facies and the soft unconsolidated marine habitats with gravel sediment and gravel sediment wave, besides the Biolitoclastic Sand (BLs) sedimentary facies and the soft unconsolidated marine habitats of sand and gravel sediment, and sand and gravel sediment wave, the latter as intermediaries between the terrigenous and marine sedimentation environments.…”
Section: Discussionsupporting
confidence: 91%
“…Dias (2000) reported that the maerl and Lithothamnium alga banks are better developed in the 8 to 60m depth interval, where the algae take better advantage of light intensity and penetration, providing the ideal conditions for their development. The records and distribution of maerl and Lithothamnium coralline algae in the study site corroborate the findings of Dias (2000) and other studies (Albino, 1999;Bourguinon et al, 2018) in this area. The maerl and Lithothamnium banks associated with fragments of rhodoliths and biolitoclastic sediments occur from 40 to 60 m deep in the submerged channels of the Costa das Algas EPA, forming the Bioclastic sand (Bs) sedimentary facies and the soft unconsolidated marine habitats with gravel sediment and gravel sediment wave, besides the Biolitoclastic Sand (BLs) sedimentary facies and the soft unconsolidated marine habitats of sand and gravel sediment, and sand and gravel sediment wave, the latter as intermediaries between the terrigenous and marine sedimentation environments.…”
Section: Discussionsupporting
confidence: 91%
“…Zimmermann and Prescott [23] accomplished the feat of combining 18 million data points from more than 200 individual sources to produce the best bathymetric model to date of the Eastern Bering Sea, enabling them to study 29 canyons in the area and to confirm the legendary status of some pinnacles. Bourguignon et al [24] used single-beam echosounders data and chart data to produce a 200-m resolution DBM by interpolating more than 150,000 points.…”
Section: Generating a Digital Bathymetric Modelmentioning
confidence: 99%
“…A geomorphological analysis was used to provide insight into the geological and ecological processes that have influenced the formation of these shelves around the two islands. Bourguignon et al [24] examined the use of seabed geomorphology and sedimentology to study the influence of sedimentary regimes on physical marine habitat distribution. They then used that information to define potential fishing grounds and predict fishing activities.…”
Section: Applicationsmentioning
confidence: 99%
“…The increasing interest and necessity for seabed habitat mapping in marine spatial planning initiatives has forced the industry of sonar makers, software developers and scientific research institutions to invest in new technology capable of producing seabed classification over regional areas [6]. Fisheries, oil and gas exploration, offshore engineering, as well as shallow and deep sea mining are examples of industries that are requiring seabed classification to support environmental risk assessments and spatial planning [6][7][8].…”
Section: Introductionmentioning
confidence: 99%